Bank Specific and Macroeconomic Determinants of Bank Profitability: Evidence from Turkey - Topak, Mehmet Sabri; Talu, Nimet Hülya (International Journal of Economics and Financial Issues, 2017)
In this study, we attempt to determine the bank-specific and macroeconomic determinants of commercial banks in Turkey over the period 2005 -2015. A balanced panel data set has been formed covering 43 periods between the dates of January 2005 and September 2015. Each period is of one-year length. According to the empirical results, bank-specific characteristics such as, the ratio of interest on loans to the interest on deposits (ILID), used as a proxy for net interest margin, the ratio of net fees and commissions revenues to total operating expenses (FCE), and relative size (SIZE) have positive and significant impact on profitability represented by ROA and ROE. On the other hand, the ratio of nonperforming loans to total loans (NPL) used as a proxy for credit risk, and capital adequacy (ESA) and the ratio of other operating expenses to total operating revenues (OEI), are negatively related to profitability. The most striking result is the fact that among all the bank-specific variables OEI has the strongest impact on profitability. This finding is consistent with the fact that since banks are limited in the determination of interest rates, they do not have control on the level of net interest revenues. Thus economising on the operating expenses is a more feasible option in increasing the profits. With respect to macroeconomic variables, real GDP and interest rate have positive impact on profitability whereas the exchange rate has a negative impact. Keywords: Bank Profitability, Performance, Turkish Banking Sector, Panel Data JEL Classifications: G21, L25, C23